A SPECIFIC POISON IN THE LIVER EXTRACTS OF RABBITS INOCULATED WITH TYPHOID AND PRODIGIOSUS BACILLI INTRAVENOUSLY - Parker, Julia T. (The Rockefeller University Press, 1918)
1. The livers of rabbits inoculated with cultures of Bacillus typhosus or Bacillus prodigiosus under certain conditions contain a toxic substance extractable with salt solution. When the toxic extracts are injected intravenously into normal rabbits the latter animals develop symptoms resembling those of anaphylactic shock and succumb. The lethal doses of the toxic extracts are far smaller than those of normal liver extract. 2. The livers of rabbits injected with typhoid antigen also yield a toxic extract. 3. Boiling as well as filtration through a Berkefeld filter only partially detoxicates the extract. 4. Tolerance to one to two lethal doses of the poisonous extracts can be induced by cautious immunization. 5. Rabbits actively immunized to Bacillus typhosus or Bacillus prodigiosus usually resist one lethal dose of the homologous liver poison; and animals tolerant to the typhoid liver poison resist one minimum lethal dose at least of Bacillus typhosus. 6. Typhoid immune serum is not detoxicating either in vivo or in vitro for the typhoid liver poison. 7. The liver poisons are specific, since rabbits actively immunized to either Bacillus typhosus or Bacillus prodigiosus withstand at least one minimum lethal dose of the homologous but not of the heterologous-liver poisons.